Characteristics of Tuberculous Spondylitis Patients at Dr. M. Djamil Padang Hospital 2018-2020 - Salsa Naudzul Athiyyah; Roni Eka Sahputra; Mohamad Reza (Frontiers on Healthcare Research)
Background: Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis which has long been known and still one of the top 10 causes of death in the world. Tuberculosis spondylitis is one of the most common extrapulmonary tuberculosis. This study aims to describe the characteristics of patients diagnosed with tuberculous spondylitis at RSUP Dr. M. Djamil Padang in 2018 – 2020.